Hegel's Pragmatic Critique and Reconstruction of Kant's System of Principles in the 1807 Phenomenology of Spirit. Issue 2 (4th September 2015) - Westphal, Kenneth R.
Abstract : Peirce's study of Kant, and later of Hegel, and Dewey's (1930) retention of much of Hegel's social philosophy are recognised idealist sources of pragmatism. Here I argue that the transition from idealism to pragmatic realism was already achieved by Hegel. Hegel's 'Objective Logic' corresponds in part to Kant's 'Transcendental Logic' ( WdL, GW 21:47.1-3). Hegel faults Kant for relegating concepts of reflection to an Appendix to his Transcendental Logic ( WdL, GW 12:19.34-38), and for treating reason as 'only dialectical' and as 'merely regulative' ( WdL, GW 12:23.12, .16-17). I present three important yet neglected features of Kant's Critique of Pure Reason which are key enthymemes undergirding Hegel's critical reconstruction of Kant's Critical philosophy (§2). I then summarise some features of the philosophical context within which Hegel begins to re-assess and reconstruct Kant's Transcendental Logic (§3), and review several key steps in this direction Hegel undertook in the 1807 Phenomenology (§4). (A related paper extends these results to Hegel's Logic and Encyclopaedia .) These points show that Hegel's reanalysis of Kant's Critical philosophy is the first and still one of the most sophisticated and adequate pragmatic — specifically pragmatic realist — accounts of the a priori .